3
$\begingroup$

I feel like there are many solutions for some proofs, and I want to make sure I'm still getting everything correct. This is the problem:

$$m^2 = n^2 (P)\quad\text{if and only if}\quad m = n (Q)\quad\text{or}\quad m = -n (Z)$$

So I need to prove $P \Rightarrow (Q \lor Z)$ and $(Q \lor Z) \Rightarrow P$ because this is a bi-conditional statement, yes? This is my proof.

Proving $P \Rightarrow (Q \lor Z)$:

Let's assume $m$ doesn't equal $n$ (proving by contra-position). It is said that $m^2 = n^2$. Take the square root of both sides and you are left with $m = n$. However, we are assuming $m$ doesn't equal $n$ so there is a contradiction.

And I pretty much did the reverse for $(Q \lor Z) \Rightarrow P$ by squaring both sides to reach the contradiction.

Is this a valid proof or is something going over my head?

$\endgroup$
4
  • 1
    $\begingroup$ It appears like you are using circular reasoning. $\endgroup$ – GoodDeeds Mar 8 '16 at 20:08
  • 1
    $\begingroup$ You may be forgetting about negative numbers. Note that for example $(-3)^2=3^2$. $\endgroup$ – André Nicolas Mar 8 '16 at 20:09
  • $\begingroup$ @AndréNicolas so how would I go about solving this? $\endgroup$ – Laugh7 Mar 8 '16 at 20:11
  • $\begingroup$ The easier part: If $m=-n$, then $m^2=(-n)^2=n^2$. For the other direction, maybe use $m^2-n^2=(m+n)(m-n)$. $\endgroup$ – André Nicolas Mar 8 '16 at 20:13
4
$\begingroup$

So I need to prove $P \to (Q \vee Z)$ and $(Q \vee Z) \to P$ because this is a bi-conditional statement, yes?

Yes.

Let's assume $m$ doesn't equal $n$ (proving by contra-position). It is said that $m^2 = n^2$. Take the square root of both sides and you are left with $m = n$. However, we are assuming $m$ doesn't equal $n$ so there is a contradiction.

There are a couple of flaws here. First, the outline of what you did is "We want to prove $R$. So assume $\neg R$. Then, blah blah blah, $R$. But we assumed $\neg R$. This is a contradiction." But you only contradicted your original assumption $\neg R$. In the middle, you proved $R$. So in proofs like that you don't need the proof-by-contradiction framework. You just did a direct proof.

Or did you? You said $m^2 = n^2 \implies m = n$ “by taking the square root of both sides.” But this isn't valid. For $2^2 = (-2)^2$ while $2 \neq -2$. So something went wrong, and it was that you lost a solution by assuming $m$ and $n$ were both positive.

With nonlinear algebraic equations, it's often safer to set the equation equal to zero and factor. In this case: $$ m^2 = n^2 \implies m^2 - n^2 = 0 \implies (m-n)(m+n) = 0 $$ Two numbers have a product of zero if and only if one of them is zero. So either $m-n = 0$ (in which case $m=n$) or $m+n=0$ (in which case $m=-n$).

$\endgroup$
3
$\begingroup$

Others have pointed out the flaws in your proof.

Hint for a correct proof: Show that $$(n-m)(n+m)=n^2-m^2$$

So if $n^2=m^2$ then what?

Bigger hint: You need to know (or prove) the rule that $ab=0$ if and only if $a=0$ or $b=0$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.